Comment on Static and spherically symmetric black holes in f(R) theories'' - Mazharimousavi, S. Habib; Halilsoy, M. (Amer Physical Soc, 2012)
consider the interesting near-horizon test'' reported in S. E. P. Bergliaffa and Y. E. C. de O. Nunes, Phys. Rev. D 84, 084006 (2011) for any static, spherically symmetric black hole solution admitted in f(R) gravity. Before adopting the necessary conditions for the test, however, revisions are needed as we point out in this Comment.